Primary Myelofibrosis Occurring during Targeted Therapy for Chronic Lymphocytic Leukemia: A Report of Two Cases - Francesco Angotzi; Andrea Visentin; Federico Scarmozzino; Alessandro Cellini; Roberta Bertorelle; Marco Pizzi; Gianni Binotto; Angelo Paolo Dei Tos; Livio Trentin (Current Oncology, 2022)
The disease course of chronic lymphocytic leukemia (CLL) is frequently characterized by the occurrence of various complications, such as second primary cancer, which can impact patients’ prognoses. While therapies for CLL have evolved tremendously in the past decades, overlooking the possibility of rare neoplasms that arise along with CLL may hinder the benefit that these therapies grant to patients. Moreover, the ability of newer therapies to alter the landscape of these complications is still largely unknown. Primary myelofibrosis (PMF) is not commonly associated with CLL, with only a few cases reported in the literature, with little information regarding the clinico-biological features and the optimal management for these associated conditions. Here, we report two unusual cases of PMF that occurred a few months after the start of therapy for CLL with targeted agents (ibrutinib and venetoclax). Both cases represented a diagnostic and therapeutic challenge, underscoring the need for clinicians to remain vigilant about the possible co-occurrence of these two hematological malignancies, especially in the era of targeted therapy for CLL.